The Effect of Digital Transformation on Employee Performance with Mediation Role of Technological Infrastructure: Evidence from Egyptian Oil and Gas Sector - Bakry, Mahmoud; Ragheb, Mohamed A.; Ragab, Aiman A. (The Arab Journal of Administration, 2024)
The goal of this research is to empirically investigate the effect digital transformation on employees’ performance with Mediation Role of technological infrastructure in the Egyptian oil and gas sector. The objectives of this research are: to investigate the relationship between digital transformation and employees’ performance, to test the relationship between digital transformation and technological infrastructure, to investigate the relationship between technological infrastructure and employees’ performance, and to examine the mediation role of technological infrastructure between digital transformation and employees’ performance. The methodology used is focused on quantitative analysis utilizing 401 online survey tool to collect the necessary data and AMOS software for structural equation model analyses (SEM). The study’s findings revealed that: all the hypotheses are supported. Finally, the study found that there is a partial mediation effect of the technological infrastructure between digital transformation and employees’ performance in Egyptian oil and gas sector.